PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN, KONTROL DIRI TERHADAP KEBERLANGSUNGAN USAHA MIKRO KECIL STAINLESS STEEL DI KABUPATEN SIDOARJO - Ramadhan, Rizky Oktavian; Zaki, Achmad; Violita, Cynthia Eka; Putrihadiningrum, Devika Cherly (JURNAL LENTERA BISNIS, 2026)
This study aims to examine the influence of literasi keuangan, inklusi keuangan and self-efficacy on the sustainability of micro and small enterprises (a study of stainless steel entrepreneurs in Sidoarjo Regency). This is a quantitative study employing an associative-causal approach using primary data collected via a questionnaire distributed to 39 respondents. The sample for this study was determined using a saturated sample. The data were analysed using PLS-SEM via SmartPLS 4. The results indicate that literasi keuangan has a negative but insignificant effect on the sustainability of MSMEs, inklusi keuangan has a positive but insignificant effect on the sustainability of MSMEs, and self-efficacy has a positive and significant effect on the sustainability of MSMEs. Thus, psychological factors in the form of business owners’ self-efficacy are the primary determinants compared to technical factors such as literasi keuangan and access to finance in this study.